Return Predictability and Trends in Earnings Surprises - Warachka, Mitchell Craig (Institutional Knowledge at Singapore Management University, 2007)
We document that trends in firm-level earnings surprises predict returns. This finding demonstrates that consistency within the sign of multiple prior quarterly earnings surprises is important for future returns. The return predictability of trends remains after controlling for the relatively large earnings surprises that define post-earnings announcement drift. Furthermore, these large earnings surprises exert a stronger influence on future returns when they occur within trends. The return predictability of trends is not attributable to consecutive earnings surprises with the same sign nor the autocorrelation in earnings surprises. Instead, as hypothesized by Rabin's (2002) theory, investors underreact to trends.